India’s plant variety and farmers’ rights legislation: potential impact on stakeholder access to genetic resources - Ramanna, Anitha (International Food Policy Research Institute, 2003)
The demand for extending intellectual property protection to agriculture in developing countries has met with counterclaims for granting farmers’ rights. Developing countries are currently attempting to fulfill these demands by evolving new IPR regimes that simultaneously protect the rights of breeders and farmers. What are the possible implications of establishing such a system of multiple rights on the utilization and exchange of genetic resources among various actors? Could the attempt to distribute ownership rights to various stakeholders pose the threat of an ‘anticommons,’ where resources are underutilized due to multiple ownership? The answers to these questions have important implications for the future of agricultural growth in developing countries. India is one of the first countries in the world to have passed a legislation granting rights to both breeders and farmers under the Protection of Plant Varieties and Farmers’ Rights Act, 2001. The law emerged from a process that attempted to incorporate the interests of various stakeholders, including private sector breeders, public sector institutions, non-governmental organizations and farmers, within the property rights framework. India’s Act allows four types of varieties to be registered reflecting the interests of actors: New Variety, Extant Variety, Essentially Derived Variety and Farmers’ Variety. Although this multiple rights system aims to equitably distribute rights, it could pose problems of overlapping claims and result in complicated bargaining requirements for utilization of varieties. A potential implication is an ‘anticommons tragedy’ where too many parties independently posses the right to exclude giving rise to underutilization of resources. India and other developing nations, in seeking to achieve the important goal of recognizing farmers’ rights, must not overlook the need for promoting exchange of agricultural resources. India’s Plant Variety and Farmers’ Right Act is significant both in the domestic and international context as several other countries are trying to establish similar legislations. Advanced nations must recognize that compelling developing countries to grant breeders rights could result in systems that run counter to their interests. Developed and developing countries must make a concerted effort to ensure that emerging IPR regimes do not restrict stakeholder access to genetic resources.